2014
DOI: 10.1136/bmjopen-2013-004293
|View full text |Cite
|
Sign up to set email alerts
|

Associations between primary healthcare and unplanned medical admissions in Norway: a multilevel analysis of the entire elderly population

Abstract: ObjectiveTo examine if individual risk of unplanned medical admissions (UMAs) was associated with municipality general practitioner (GP) or long-term care (LTC) volume among the entire Norwegian elderly population.DesignCross-sectional population-based study.Setting428 of 430 Norwegian municipalities in 2009.ParticipantsAll Norwegians aged ≥65 years (n=721 915; 56% women—15% of the total population).Main outcome measureIndividual risk of UMA.ResultsUsing a multilevel analytical framework, consisting of individ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
11
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(12 citation statements)
references
References 42 publications
(36 reference statements)
1
11
0
Order By: Relevance
“…The lack of a significant association between the supply of GP services and preventable hospitalizations was unexpected, because much of the literature has demonstrated inverse associations. 7 9 , 40 However, results have been inconsistent, 19 – 21 , 28 and much of the research has used practitioner headcount measures or self-rated access to care rather than more objective measures of effective supply. Most of the existing research was performed in the United States with few studies in Australia.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The lack of a significant association between the supply of GP services and preventable hospitalizations was unexpected, because much of the literature has demonstrated inverse associations. 7 9 , 40 However, results have been inconsistent, 19 – 21 , 28 and much of the research has used practitioner headcount measures or self-rated access to care rather than more objective measures of effective supply. Most of the existing research was performed in the United States with few studies in Australia.…”
Section: Discussionmentioning
confidence: 99%
“…The core strengths of this study include the availability of detailed person-level information with linked hospital admissions data, and the use of multilevel modelling to examine how population composition influences geographic variation in admission. Reliable area-level data that is representative of the population, such as disease prevalence, can be difficult to obtain, 47 and while a number of studies have had either detailed person-level data, 23 , 24 or used multilevel modelling to incorporate individual factors into small-area analyses of preventable admission, 7 , 27 , 28 this is the first study to our knowledge to incorporate both. This study is also one of the few to present results stratified by both major categories and individual conditions 6 , 11 , 15 , 20 , 42 that are included in the indicator.…”
Section: Discussionmentioning
confidence: 99%
“…Although primary healthcare is the cornerstone of the healthcare system, its association with hospital admissions is paradoxical. [43][44][45][46] Another study from Quebec, Canada, showed that more frequent visits to the primary physician was associated with decreased unplanned admission in elderly people. 47 Yet another study showed that regular doctor visit was associated with lower rates of emergency department visit in the older population, after controlling for diagnoses of patients.…”
Section: Discussionmentioning
confidence: 99%
“…For example, Voigtländer et al 2010made such an adjustment to their baseline model when analysing the influence of regional and neighbourhood deprivation on self-rated health. Another example is provided by Deraas et al (2014) who fitted a baseline model including age and sex in their study of the influence of primary care on unplanned hospital admissions. Cole et al (2009) studied mental health outcomes and musculoskeletal disorders in a cohort of healthcare workers.…”
Section: The Baseline Modelmentioning
confidence: 99%